Laboratory determination of resilient modulus for flexible pavement design - Witczak, Matthew W. (Research results digest (National Cooperative Highway Research Program), 2004)
"This digest represents key findings from NCHRP Project 1-28A, 'Harmonized test methods for laboratory determination of resilient modulus for flexible pavement design,' conducted by the Univerisity of Maryland-College Park. The digest is an abridgement of portions of the project final report by the princincipal investigator, Matthew W. Witczak ... "--P. [1].